Multi-objective evaluation method for combined cycle power plant start-up. (September 2020) - Shirakawa, Masakazu; Arakawa, Masao
Abstract: With the increase in the available types of renewable energy sources, such as wind and solar radiation, it is essential that thermal power plants operate more flexibly in order to stabilize their power system. For practical flexible operation, operators (or designers) need to consider multiple evaluation indicators. This study proposes a multi-objective evaluation method for plant operation using self-organizing maps and data envelopment analysis. Pareto-optimal solutions extracted from the results of start-up dynamic simulation of a combined cycle power plant verify the efficacy of the proposed method. Additionally, we propose flexible plant operations based on the multiple-criteria decision-making system and report the results of its economic assessment via Monte Carlo simulations. Highlights: Need to consider multiple evaluation indicators for flexible plant operations Develop a multi-objective evaluation method for plant operation Extract Pareto-optimal solutions from the results of power plant start-up Discuss flexible plant operations based on the multiple-criteria decision-making system